PENGAMBILAN KEPUTUSAN PETANI DALAM PEMBELIAN BENIH PADI DI KIOS AGROTANI DESA CENLECEN KECAMATAN PAKONG KABUPATEN PAMEKASAN - suryadi mohammad; Sustiyana Sustiyana; Mohammad Shoimus Sholeh (Universitas Islam Madura, 2021)
The purpose of this study was to identify and analyze the factors that influence farmers' decision making to buy rice seeds at the Agrotani kiosk in Cenlecen Village, Pakong District, Pamekasan Regency. This research is a survey research, using respondents who were selected using the accidental sampling method and selected 60 respondents who were met by chance with predetermined criteria. The data were analyzed descriptively and qualitatively. The results showed that from the results of the validity and reliability test all items from each variable were valid and reliable so that the data could be used for logistic regression testing. The results of the logistic regression test showed that the price and product variables had a significant effect on farmers' decision making in buying rice seeds at the Agrotani kiosk with an error rate of 10%, while the service, location and promotion variables had no significant effect. Then, based on the classification table, the logit results show the number of respondents who bought as many as 29 people but there are 9 people who probably will not buy the product again. From these results, it is recommended for further researchers to develop this research by considering other variables which are other variables outside the variables that have been included in this study